Sensing and photocatalytic properties of nanosized Cu(I)CN organotin supramolecular coordination polymer based on pyrazine. (24th July 2019) - Etaiw, Safaa El‐din H.; Marie, Hassan; Shalaby, Elsayed M.; Farag, Rabie S.; Elsharqawy, Fatma A.
Abstract : Orange prismatic crystals of the supramolecular coordination polymer (SCP) ∞ 3 [Cu(CN)2 (Me3 Sn)(Pyz)], SCP1, were synthesized using a self‐assembly method under ambient conditions. Nanosized 1 was obtained using the same molar ratio in water by ultrasonic irradiation. SCP1 was characterized using single‐crystal X‐ray diffraction, elemental analysis, thermal analysis and Fourier transform infrared spectroscopy. SCP1 and its nanosized 1 particles were also examined using powder X‐ay diffraction and scanning electron microscopy. The luminescence emission of SCP1 was studied as well as its use as a sensor for the detection of common organic solvents and metal ions. Also, the catalytic activities of nanosized 1 towards various organic dyes were investigated under ambient conditions, UV irradiation and ultrasonic irradiation. Nanosized 1 as a heterogeneous nanoparticle catalyst exhibits high catalytic activity for the degradation of eosin‐Y and acid blue dyes. The mechanism of degradation investigated using various scavenger techniques is proposed and discussed. The catalytic oxidation process is mainly caused by OH radicals. Abstract : Visualization of the three‐dimensional network structure of SCP1 in the ab ‐plane showing the multi‐fold equivalent interpenetrating frames of SCP1 .